2004
DOI: 10.1063/1.1649811
|View full text |Cite
|
Sign up to set email alerts
|

Role of marble microstructure in near-infrared laser-induced damage during laser cleaning

Abstract: When marble is cleaned by nanosecond neodymium yttrium-aluminum-garnet lasers ͑1064 nm͒, strongly absorbing surface contaminants are removed at fluences substantially below the damage threshold for the much less absorptive marble substrate. Recent studies have shown, however, that unacceptable roughening of the marble surface also may occur at low fluences due to removal of individual grains. In order to elucidate this effect, we have compared the low-fluence response of marbles with two different grain sizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It probably arises from thermal reactions in iron-rich minerals that give this dramatic change in color. Other authors 13 have found mechanical damage and roughening of marble surfaces at irradiative fluences lower than that used in this research. Laser clean can also increase surface roughness, but the expected changes would be towards lighter and more saturated tones.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It probably arises from thermal reactions in iron-rich minerals that give this dramatic change in color. Other authors 13 have found mechanical damage and roughening of marble surfaces at irradiative fluences lower than that used in this research. Laser clean can also increase surface roughness, but the expected changes would be towards lighter and more saturated tones.…”
Section: Discussionmentioning
confidence: 93%
“…Chromatic modifications in laser-treated dry-stone surfaces are usually attributed to changes in the oxidation state of iron compounds. 11 Moreover, laser cleaning could also result in variations in surface roughness 13 that could alter stone color. 2 The damage thresholds for stone also depend on the physical state of the stone surface (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the effective stresses are 4.23 and 1.68 MPa in the case of mirabilite crystallization in the absence and in the presence of DTPMP. The tensile strength of the tested limestone is 1.8 ± 0.5 MPa . Salt damage occurs when the effective stress due to generation of salt crystallization pressure in a porous material is higher than the tensile stress. , It follows that the reduction in crystallization pressure associated with the presence of DTPMP explains the reduction in damage to the porous stone support observed in our macroscale salt crystallization tests.…”
Section: Resultsmentioning
confidence: 56%
“…Acc.V Spot Magri Det WD 10.0 kV 4.0 500x SE 11.6 CACTI 50 tan The success of this method lies in its relatively low irradiance. This reduces the heating of the stone surface, and, at the same time, the sample cools down between both laser passes.…”
mentioning
confidence: 99%